Collaborative Governance and Actor Communication in Bandung Science Techno Park - Muhammad Arief Mubarak; Nandang Alamsah Deliarnoor; Dede Sri Kartini; Salsabila Humaira (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2025)
This study explores the dynamics of stakeholder communication in the collaborative process of managing the Science and Techno Park Bandung Institute of Technology (STP ITB) using the Ansell and Gash Collaborative Governance framework (2008). The main focus is on five core elements of communication in the collaborative process: face-to-face dialogue, trust building, commitment to the process, shared understanding, and intermediate outcomes. Qualitative research methods with in-depth interviews, are used to uncover communicaton patterns, conflict mediation, and evaluation mechanisms implemented by STP ITB. The results show that regular coordination forums and thematic workshops facilitate synchronization of visions between parties, while procedural transparency and evidence-based trust strengthen partner trust. Long-term partner selection policies also the formulation of Memorandums of Understanding and Cooperation Agreements periodically evaluated foster collective commitment. Intermediate outcomes such as the operation of ready-to-use laboratories, increasing the number of incubated startups, and patent registration are drivers of collaboration momentum. However, the participation of regional actors and the capacity of Micro, Small, and Medium Enterprises still need to be strengthened. These findings recommend expanding invitations for cross-regional dialogue, developing mentoring programs for weak actors, and sharpening incentive mechanisms to increase the inclusiveness and sustainability of the innovation ecosystem in Bandung.